Working paper: Literature review on potential options for livestock feed improvement in Malawi - Chikwanha, Obert; Chiduwa, Mazvita; Malunga, Innocent; Chimonyo, Vimbayi; Mhlanga, Blessing; Nyagumbo, Isaiah; Thierfelder, Christian (International Maize and Wheat Improvement Center, 2024)
Smallholder farmers in Malawi are confronted with many challenges, encompassing both biophysical and socioeconomic aspects, which negatively impact their livelihoods. Unfortunately, these challenges are often addressed in fragmented approaches, lacking a holistic perspective, that prioritises isolated components and dimensions of their livelihoods. Instead of prioritising the improvement of nutrient content in forages and grains, crucial for both quantity and quality of protein, interventions tend to overlook this aspect. Consequently, food security remains compromised, exacerbating issues related to hidden hunger. This study was designed to explore opportunities in the contrasting communities within the Mangochi district, characterised by aridity, with the higher potential (semi-arid) sites of Kasungu where CIMMYT implements activities under Mixed Farming Systems initiatives. The study assessed various forage options within the framework of sustainable intensification aimed at enhancing livelihoods across diverse landscapes in Malawi, highlighting opportunities for maximising synergistic benefits and minimising potential trade-offs.